2021
DOI: 10.3390/ma14237305
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts Adhesion to Laser-Modified Titanium Surfaces—A Systematic Review

Abstract: Objective: Laser treatment has been recently introduced in many fields of implant dentistry. The systematic review tried to address the question: “How does laser modification of titanium surface influence fibroblast adhesion?”. Methods: An electronic search of the PubMed and Scopus databases was performed. The following keywords were used: (laser) AND (fibroblast) AND (titanium) AND (implant OR disc) AND (proliferation OR adhesion). Initially, 136 studies were found. Ten studies met the inclusion criteria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…2,19 Furthermore, HGFs seeded onto Sr-coated and uncoated Ti surfaces were not morphologically different from untreated control fibroblast cells, further affirming the biocompatibility of both Sr and Ti. The adherent cells on Sr-coated Ti surfaces exhibited spindle-shaped (fusiform) morphology with cellular bridges that grew as Previous studies have shown that this cell morphology has a higher ability for attachment than round cells, 25 indicating that the fusiform morphology of adhered fibroblasts in this study might be associated with more cell adhesion and proliferation, and hence could provide better circumstances for successful implant treatment. Moreover, this study determined the quantity of live cells present in Sr-coated Ti surfaces by assessing their cell viability.…”
Section: Discussionsupporting
confidence: 55%
“…2,19 Furthermore, HGFs seeded onto Sr-coated and uncoated Ti surfaces were not morphologically different from untreated control fibroblast cells, further affirming the biocompatibility of both Sr and Ti. The adherent cells on Sr-coated Ti surfaces exhibited spindle-shaped (fusiform) morphology with cellular bridges that grew as Previous studies have shown that this cell morphology has a higher ability for attachment than round cells, 25 indicating that the fusiform morphology of adhered fibroblasts in this study might be associated with more cell adhesion and proliferation, and hence could provide better circumstances for successful implant treatment. Moreover, this study determined the quantity of live cells present in Sr-coated Ti surfaces by assessing their cell viability.…”
Section: Discussionsupporting
confidence: 55%
“…Conventional dental implants employed for such purposes are fabricated from titanium and its alloys [34]. The strategic utilization of titanium and its derivatives is predicated on their capacity to ensure biocompatibility, corrosion resistance, commendable physical properties, and an effective interaction with body cells, facilitating their adhesion to the implant surface [35,36]. Dentistry, as an ever-evolving scientific discipline, steadfastly pursues the advancement of dental materials and treatment outcomes [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical studies in patients are essential to prove the effectiveness of any material. Furthermore, in order to keep the peri-implant health condition, mechanical debridement therapy was periodically recommended to the patients, avoiding peri-implant diseases, keeping the stabilization of the surrounding hard and soft tissues [ 27 ], which can also have influence by the type of implant [ 28 ]. In addition, if necessary, the adjunctive use of ozone, glycine/erythritol, probiotics, and chlorhexidine treatment may be considered [ 29 ].…”
Section: Discussionmentioning
confidence: 99%